IMPACT OF WORK FROM HOME POLICY IN THE BANKING SECTOR ON EMPLOYEE PERFORMANCE AND MOTIVATION - Fuadiputra, Iqbal Ramadhani; Arifiani, Ratya Shafira (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The pandemic that is still continuing has made several business actors carry out various kinds of policy innovations so that their business continues to run, one of which is the implementation of Work From Home as one of the solutions. This is no exception in the banking sector whose services have switched to online, making employees change their habits at work who used to do their work offline now have to work at home to provide maximum service to the community. In addition to measuring the impact of Work From Home on employee performance, the research also examines the extent of employee motivation when they carry out Work From Home regulations in their offices. The research uses quantitative research methods which are also supported by various supporting literature reviews. The analysis tool in this study uses path analysis with SmartPLS 3.0 software. Respondents in this study were banking sector employees in the East Java region. The results showed that Work From Home has an effect on performance and Work Form Home is significant to worker motivation. Research is also supported by data based on viewer that has been done.